Africa-Wide Conference on the Improved NextGen Approach (Ghana's Participation) - Martey, Francisca; Opoku, Nana Kofi; Lazia, Jeremiah Z. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The International Research Institute for Climate and Society (IRI), as part of Columbia Climate School at Columbia University organized an intensive three-week conference on subseasonal and seasonal forecasting using the updated NextGen (PyCPT2.5.5) approach at its Lamont-Doherty Earth Observatory campus in Palisades, New York with staff from ICPAC and AGRHYMET, as well as the national meteorological services of six AICCRA countries and Lesotho. The NextGen approach, which is used to produce climate forecasts across timescales, is based on more than 25 years of research at the IRI, and is being implemented in different countries across the world.